2019
DOI: 10.1016/j.chiabu.2019.104074
|View full text |Cite
|
Sign up to set email alerts
|

Coerced and forced sexual initiation and its association with negative health outcomes among youth: Results from the Nigeria, Uganda, and Zambia Violence Against Children Surveys

Abstract: Introduction: Coerced and forced sexual initiation (FSI) can have detrimental effects on children and youth. Understanding health outcomes that are associated with experiences of FSI is important for developing appropriate strategies for prevention and treatment of FSI and its consequences. Methods: The Violence Against Children Surveys were conducted in Nigeria, Uganda, and Zambia in 2014 and 2015. We examined the prevalence of FSI and its consequences (sexual high-risk behaviors, violence experiences, ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Consistent with findings of various previous studies [2][3][4][5][10][11][12], this study found among men and women that physical IPV and/or sexual violence victimization was associated with sexual risk behaviour (having had multiple sexual partners, alcohol use in the context of sex, diagnosed with HIV and pregnancy), and violence related behaviour (been in a physical fight and carried a weapon). In agreement with previous findings [2,5,6,[8][9][10][11][12][13][16][17][18][19][20], physical IPV and/or sexual violence victimization was overall and among women associated with all 5 mental health indicators (depression, loneliness, PTSD, sleeping problem and short sleep) and among men 2 poor mental health indicators (PTSD and sleeping problem), and overall victimization was associated with 3 addictive behaviours (alcohol, tobacco and drug use), among women 2 addictive behaviours (binge drinking and tobacco use) and among men 2 addictive behaviours (tobacco use and drug use).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with findings of various previous studies [2][3][4][5][10][11][12], this study found among men and women that physical IPV and/or sexual violence victimization was associated with sexual risk behaviour (having had multiple sexual partners, alcohol use in the context of sex, diagnosed with HIV and pregnancy), and violence related behaviour (been in a physical fight and carried a weapon). In agreement with previous findings [2,5,6,[8][9][10][11][12][13][16][17][18][19][20], physical IPV and/or sexual violence victimization was overall and among women associated with all 5 mental health indicators (depression, loneliness, PTSD, sleeping problem and short sleep) and among men 2 poor mental health indicators (PTSD and sleeping problem), and overall victimization was associated with 3 addictive behaviours (alcohol, tobacco and drug use), among women 2 addictive behaviours (binge drinking and tobacco use) and among men 2 addictive behaviours (tobacco use and drug use).…”
Section: Discussionsupporting
confidence: 93%
“…Various studies have identified that a history physical IPV and/or sexual violence victimization among male and/or female adolescents or emerging adults is associated with sexual risk behaviours, violence related behaviours, poor mental health, substance use, other health risk behaviours, poor health status and poor academic performance. Sexual risk behaviour among adolescents and emerging adults may include, multiple sexual partners [2][3][4], unprotected sex [5][6][7][8][9], pregnancy [4][5][6][7]10], and sexually transmitted infections including HIV [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the wide range of negative consequences of IPV for women include loss of pregnancy, through stillbirths and miscarriages, and contraction of sexually transmitted infections ( Durevall & Lindskog, 2015 ). Women who suffer from IPV are also more likely to report high levels of depression, post-traumatic stress disorder, psychological distress, as well as suicidal thoughts ( Mason & Lodrick, 2013 ; Nguyen et al, 2019 ; Ogunwale & Oshiname, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from sub-Saharan Africa suggest that, while a significant number of adolescents have their first sexual experience at an early age (ranging from 2.0 to 27.0% of adolescents under age 15) [2], in many cases they do not use any form of protection to prevent pregnancy or sexually transmitted infections [3,4]. In addition, not all sexual experiences among adolescents are consensual, since the prevalence of coerced sex and sexual abuse at this age remains high (approximately 16% in Zambia) [5,6].…”
Section: Introductionmentioning
confidence: 99%